Genetic parameters of growth of Ethiopian Boran cattle - Arnason, T.; Kassa-Mersha, H. (Cambridge University Press, 1987)
Records on birth weight and pre-weaning growth of 3959 Boran calves, which were progeny of 51 sires and 979 dams, were analysed by least-squares analysis of variance. The vaiance components for sires, dams and maternal grandsires were estimated from the data. On the basis of assumed genetic correlations -0.44 and -0.55 between direct and maternal effects on birth weight and weaning weight, respectively, the maternal genetic component and the genetic covariance between direct and maternal effects were estimated. The heritabilities for direct effects on birth weight and weaning weight were 0.11 and 0.22, respectively, while the heritabilities of maternal effects were estimated as 0.02 and 0.11, respectively for the same traits. Selection indices for direct and maternal genetic components of weaning weight were constructed for practical use. These selection indices combined information on the individual, the parents and sibs.